The Financial Performance of PT Sinar Mas Agro Resources and Technology Tbk - Ambarita, Dina Devianty; Nasution, Wendi Amsuri (Dinasti International Journal of Economics, Finance & Accounting, 2024)
PT SMART Tbk was established on June 18, 1962, as PT Airline Plantation Sumcama Padang Halaban and commenced its commercial activities in the same year. Expanding the company's land holdings indicates its classification as a lucrative entity. Upon examining the company's financial statistics, two potential outcomes emerge: positive or negative. Since it does not eliminate the potential for expansion to be funded by corporate debt, this research aims to conduct a financial performance analysis of PT Sinar Mas Agro Resources and Technology Tbk. The research utilizes documentation analysis as the data collection approach, specifically gathering financial data from firm-published documents on the Indonesian Stock Exchange. PT SMART Tbk's primary objective is to enhance its current assets and cash reserves, reduce liabilities, grow its overall assets, meet its existing debt obligations, and improve its financial performance. Research is conducted to enhance firm performance by boosting sales, capital, and assets.